Hubungan Efek Samping Kemoterapi dengan Kualitas Hidup Pasien Kanker Payudara di Rumah Sakit Kanker Dharmais Provinsi DKI Jakarta Tahun 2023 - Johanes Parasian; Yuni Susilowati; Nuryanti Nuryanti; Zahrah Maulidia Septimar; Siti Haeriyah (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2024)
Background: Data from the 2018 Global Burden of Cancer Study (Globocan) noted that breast cancer is one of the most common types of cancer in the world with an incidence of 11.6% and the number of new cases of 2,089 million. The American Cancer Society, in 2018 also reported that breast cancer is the most common cancer in women in the world with an incidence rate of 40 per 100,000, new cases of 30.5% with a death rate of 21.5% per year. Chemotherapy is one of the most common treatments for breast cancer. Chemotherapy has several effects that can worsen the patient's functional status, such as in work, self-care, and maintenance of family or social roles. This can make the quality of life of cancer patients decrease. Research objective: To determine the relationship between side effects of chemotherapy and the quality of life of breast cancer patients. Research method: Correlational quantitative research with a cross sectional approach. The total sample is 103 breast cancer patients taken by total sampling technique. Results: The results of univariate analysis showed that most of the breast cancer patients undergoing chemotherapy at Dharmais Cancer Hospital had a good quality of life (54.4%), and most of them were adaptive to the side effects of chemotherapy (53.4%). The results of the bivariate analysis showed that there was a significant relationship between the side effects of chemotherapy and the quality of life of breast cancer patients at the Dharmais Cancer Hospital in 2023 (p value: 0.001). Conclusions and Suggestions: It is hoped that the hospital will implement SOPs for nurses so that they play a greater role in improving the quality of life of breast cancer patients by providing holistic nursing care, especially in the physical health domain.